Factors that influence enrollment in syringe services programs in rural areas: a qualitative study among program clients in Appalachian Kentucky - Umedjon Ibragimov; Katherine E. Cooper; Evan Batty; April M. Ballard; Monica Fadanelli; Skylar B. Gross; Emma M. Klein; Scott Lockard; April M. Young; Hannah L. F. Cooper (BMC, 2021)
Abstract Background Enrolling sufficient number of people who inject drugs (PWID) into syringe services programs (SSP) is important to curtail outbreaks of drug-related harms. Still, little is known about barriers and facilitators to SSP enrollment in rural areas with no history of such programs. This study's purpose was to develop a grounded theory of the role of the risk environment and individual characteristics of PWID in shaping SSP enrollment in rural Kentucky. Methods We conducted one-on-one semi-structured interviews with 41 clients of 5 SSPs that were established in rural counties in Appalachian Kentucky in 2017-2018. Interviews covered PWID needs, the process of becoming aware of SSPs, and barriers and facilitators to SSP enrollment. Applying constructivist grounded theory methods and guided by the Intersectional Risk Environment Framework (IREF), we applied open, axial and selective coding to develop the grounded theory. Results Stigma, a feature of IREF's meso-level social domain, is the main factor hampering SSP enrollment. PWID hesitated to visit SSPs because of internalized stigma and because of anticipated stigma from police, friends, family and healthcare providers. Fear of stigma was often mitigated or amplified by a constellation of meso-level environmental factors related to healthcare (e.g., SSPs) and social (PWID networks) domains and by PWID's individual characteristics. SSPs mitigated stigma as a barrier to enrollment by providing low threshold services in a friendly atmosphere, and by offering their clients program IDs to protect them from paraphernalia charges. SSP clients spread positive information about the program within PWID networks and helped their hesitant peers to enroll by accompanying them to SSPs. Individual characteristics, including child custody, employment or high social status, made certain PWID more susceptible to drug-related stigma and hence more likely to delay SSP enrollment. Conclusions Features of the social and healthcare environments operating at the meso-level, as well as PWID's individual characteristics, appear to enhance or mitigate the effect of stigma as a barrier to SSP enrollment. SSPs opening in locations with high stigma against PWID need to ensure low threshold and friendly services, protect their clients from police and mobilize PWID networks to promote enrollment.